Kinetics of Oxidation of Furfural by N-bromosaccharin in Aqueous Acetic Acid Medium - Ramkumar, B. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of furfural by N-bromosaccharin (NBSA) has been studied in 50% (v/v) acetic acid-water mixtures. The reaction shows first order dependence each in [NBSA], [Furfural] and [H+] ions. Increase in acetic acid content of the solvent medium decreases the rate of reaction. Activation parameters have been calculated. A suitable mechanism has been proposed in consistence with the kinetic data.